Mandibular ramus remodeling after vertical osteotomy: a three-dimensional quantitative and qualitative assessment with sequential segmental-marrow superimposition - Sang-Hwy Lee; Bong Chul Kim; Hoon Cho; Nam-Kyoo Kim; Jong-Ki Huh; Hyung Seog Yu; Sang-Hoon Kang (BMC Oral Health)
Abstract Background The intraoral vertical ramus osteotomy (IVRO) is a surgical technique for prognathic or asymmetric mandible. We wanted to quantitatively and qualitatively analyze the three-dimensional (3D) remodeling pattern of the mandibular ramus one year after IVRO. Methods We reconstructed 3D mandibular models using 3D CT data from 108 IVRO hemi-mandibles of 54 subjects. The immediate postoperative (Imm) proximal and distal segments were separated and individually superimposed to one-year postoperative (Post) mandible by employing a direct segmental-isolated marrow superimposition. Results Analysis showed extensive regional bone resorption and apposition resulting in a remodeled Post ramus; the more overlapping patterns of group of A (lateral type) and B (lateral/proximal type) suffered resorption-dominant remodeling compared with the less-overlapped group C (proximal type) and D (gap type), while the level of apposition was similar for all groups. Post ramus showed different levels of sigmoid notch filling with newly-formed bones and various shapes of new bony projections at the posterior border of the medial ramus. Bone resorption in group A was significantly and negatively correlated with protrusion delta (the difference between the postoperative and preoperative protrusive mandibular movement ranges), and bone apposition was positive with amount of postoperative maximum opening. Conclusion All results indicate dynamic remodeling of the Imm ramus after IVRO in relation to the segmental overlapping pattern to form a smooth and continuous skeletal surface. The new superimposition method of direct segmental overlapping could detect the detailed remodeling pattern.